2018
DOI: 10.1016/j.electstud.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

How voters assess elite-educated politicians: A survey experiment

Abstract: Are politicians with elite backgrounds more electable? In this article, we test whether being an elite is a net positive or negative in running for public office via an original survey experiment that manipulates one of the most salient indicators of eliteness in American life: university education. We find that liberals, but not conservatives, perceive politicians who attended elite schools to be more competent. Meanwhile, conservatives, but not liberals, perceive politicians who attended elite schools to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…For example, volunteers may be more motivated by academic interest than the general public, or their high levels of intrinsic motivation may be associated with unrepresentative attitudes and behaviors [28]. Given that studies from volunteer pools are already appearing in prominent social science journals (e.g., [29–31]), these possibilities should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, volunteers may be more motivated by academic interest than the general public, or their high levels of intrinsic motivation may be associated with unrepresentative attitudes and behaviors [28]. Given that studies from volunteer pools are already appearing in prominent social science journals (e.g., [29–31]), these possibilities should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Our results add to a sizable literature on candidate experiments (Campbell & Cowley, 2014;Carnes & Sadin, 2015;Gift & Lastra-Anadón, 2018;Kahn, 1994;Sigelman et al, 1995) by examining how an important background traitspecifically, whether politicians send their children to public or private school-affects ballot box appeal. While prior research has analyzed the effect of family compositionincluding whether politicians have children-on electability, we find that decisions regarding families can condition how voters perceive politicians.…”
mentioning
confidence: 66%
“…Various studies have asked why Congress consists of mostly high‐SES members (e.g., Carnes ; Gift and Lastra‐Anadon ). Our experiments join a growing body of evidence suggesting that voter demand is not one of the reasons (Campbell and Cowley ; Carnes and Lupu ; Hainmueller, Hopkins, and Yamamoto ; Wüest and Pontusson ).…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of candidate experiment studies has examined the impact of candidate SES on voters. However, most of these studies have focused on candidate occupation (Campbell and Cowley ; Carnes and Lupu ; McDermott ) or education (Carnes and Lupu ; Gift and Lastra‐Anadon ; Hainmueller, Hopkins, and Yamamoto ). For example, Carnes and Lupu () found that subjects viewed a factory‐worker candidate as more “relatable” than a business‐owner candidate.…”
Section: Theoretical Background and Expectationsmentioning
confidence: 99%
See 1 more Smart Citation